(untitled) (Studia Prawnicze / The Legal Studies, 1969)
Autor artykułu prezentuje zagadnienia prawne i ekonomiczne pojęcia integracji międzynarodowej. Praca ma charakter interdyscyplinarny, ponieważ łączy kwestie dotyczące zarówno nauk ekonomicznych, prawa międzynarodowego publicznego jak i nauk politycznych. Celem pracy jest porównanie różnych koncepcji teoretycznych międzynarodowej integracji gospodarczej oraz międzynarodowej organizacji gospodarczej o celu kwalifikowalnym jako integracyjny. Ze względu na mnogość koncepcji teoretycznych, Autor skupia się na przedstawieniu szkoły neoliberalnej, skutków integracji gospodarczej dla stosunków międzypaństwowych, teorii formalnej, powiązań rzeczowych, definicji integracji gospodarczej oraz na różnicach funkcjonowania integracji gospodarczej pomiędzy krajami kapitalistycznymi a socjalistycznymi. The author of this article presents the legal and economic issues of the concept of international integration. The work is interdisciplinary in that it brings together issues relating to both economic sciences, public international law and political sciences. The purpose of this paper is to compare the different theoretical concepts of international economic integration and of an international economic organisation with a qualifying objective of integration. Due to the multitude of theoretical concepts, the author focuses on presenting the neo-liberal school, the effects of economic integration on inter-state relations, formal theory, material linkages, definitions of economic integration and the differences in the functioning of economic integration between capitalist and socialist countries.